PENGARUH RENDAMAN AIR HANGAT DENGAN GARAM EPSOM TERHADAP REDUKSI PEMBENGKAKAN KAKI PADA IBU HAMIL TRIMESTER III - Ela Rohaeni; Iis; Lia Haliatina (Jurnal Medicare, 2026)
Leg swelling (edema) is a common complaint among pregnant women in the third trimester due to excess fluid accumulation in the interstitial tissue. This condition can cause discomfort and interfere with activities if left untreated. One non-pharmacological therapy that can be used is a warm water soak with Epsom salts, which contain magnesium and sulfate, which function to improve blood circulation, reduce fluid retention, and provide a relaxing effect. This study aimed to determine the effect of a warm water soak with Epsom salts on reducing leg swelling in pregnant women in the third trimester at the Tanjungmedar Community Health Center in Sumedang Regency.The study used a pre-experimental, one-group pretest-posttest design, with a population of all pregnant women in the third trimester experiencing edema. A sample of 34 respondents was selected using a purposive sampling technique. Data analysis used a Paired Samples Test.The results showed a significant difference between the degree of swelling before and after treatment with a p-value of 0.000 (p < 0.05). The conclusion of this study is that a warm water soak with Epsom salts is effective in reducing the degree of leg swelling in pregnant women in the third trimester. It is hoped that this intervention can be implemented as self-care or in primary healthcare settings to improve maternal comfort during pregnancy.